Guest - Zamora, Felicia, author; Beachy-Quick, Dan, advisor; Cooperman, Matthew, committee member; Moseman, Eleanor, committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Keywords: ecopoetics; human relation to nature; poetry